Analisis Pengaruh Threat Emotion Konsumen dan Brand Trust Pada Keputusan Pembelian Produk HIT Aerosol (Studi Kasus Di Hypermart Plaza Mulia Samarinda) - Sulistiyowati Sulistiyowati; Jusuf Kuleh; Gusti Noorlitaria Achmad (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
This study aimed to analyze the influence of Threat Emotions and Brand Trust to the Buying Decision. The independent variables in this study are threat emotions and brand trust, while the dependent variable in this study is buying decision. The type of research that is used is quantitative research. The research was conducted on customers of Hypermart Plaza Mulia Samarinda who have made a purchase HIT Aerosol. The sampling technique used purposive sampling. Data analysis techniques in this study using quantitative analysis. This study shows that threat emotion and brand trust has a significant influence to the buying decision.Key Words: Threat Emotion, Brand Trust, Buying Decision.